2021
DOI: 10.1055/s-0041-1740132
|View full text |Cite
|
Sign up to set email alerts
|

Axilla versus Wrist as the Recipient Site in Vascularized Lymph Node Transfer for Breast Cancer-Related Lymphedema: A Systematic Review and Meta-Analysis

Abstract: Background Vascularized lymph node transfers (VLNT) are being used with increasing frequency for the treatment of breast cancer-related lymphedema (BCRL). However, there is a lack of consensus in the surgical field as to which recipient site should be utilized. We, therefore, aim to assess the evidence comparing the wrist and axilla as recipient sites for VLNT in BCRL. Methods We conducted a systematic literature review to compare the wrist and axilla as recipient sites for VLNT in BCRL. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, in a recent meta-analysis evaluating the effect of the recipient site for VLNT on BCRL, comparable outcomes were found comparing the wrist and the axilla as recipient sites. The CRR (wrist, 42.1% versus axilla, 51.5%) or excess volume reduction rates were comparable between groups (wrist 35.6% and axilla 48.8%) (level of evidence: II) ( 74 ). Likewise, similar outcomes were found for the rate of postoperative discontinuation of compression garments, reduction rate of infection episodes per year, and overall pooled complication rates when comparing the different recipient sites (level of evidence: II) ( 74 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, in a recent meta-analysis evaluating the effect of the recipient site for VLNT on BCRL, comparable outcomes were found comparing the wrist and the axilla as recipient sites. The CRR (wrist, 42.1% versus axilla, 51.5%) or excess volume reduction rates were comparable between groups (wrist 35.6% and axilla 48.8%) (level of evidence: II) ( 74 ). Likewise, similar outcomes were found for the rate of postoperative discontinuation of compression garments, reduction rate of infection episodes per year, and overall pooled complication rates when comparing the different recipient sites (level of evidence: II) ( 74 ).…”
Section: Discussionmentioning
confidence: 89%
“…The CRR (wrist, 42.1% versus axilla, 51.5%) or excess volume reduction rates were comparable between groups (wrist 35.6% and axilla 48.8%) (level of evidence: II) ( 74 ). Likewise, similar outcomes were found for the rate of postoperative discontinuation of compression garments, reduction rate of infection episodes per year, and overall pooled complication rates when comparing the different recipient sites (level of evidence: II) ( 74 ). Of note, when selecting the wrist as the recipient site, a dorsal placement seemed to generate a significant reduction in limb circumference at 12 months (P=0.04), improved venous outflow (P<0.0001), and better patient-reported outcomes using the LYMQOL (P=0.04) compared to a volar inset (level of evidence: IV) ( 60 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…21 Important papers may not have been cited to make the top 100, but are more recent and are likely to have an impact on the field of lymphedema such as studies of different recipient sites for vascularized lymph node transfer, prophylaxis of extremity lymphedema related to cancer, and various surgical treatments used for extremity lymphedema. [22][23][24] Authors may also have a particular preference of which citations they choose, and citation count is time-dependent, where recently published papers do not have as much opportunity to be cited as older studies. In addition, if the citation was referenced in a positive or negative manner is not considered.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, heterotopic placement may be more efficient as it is facile with the gravity, although esthetic outcome is usually poorer with more visible scars [88]. However, meta-analysis made by Chocron et al found non-inferiority between axilla and wrist as a recipient site in a limb circumference [90]. Choosing the donor site may bring difficulties as there are lack of studies comparing outcomes for each region.…”
Section: Vascularized Lymph Node Transfer (Vlnt)mentioning
confidence: 99%